Effect of single dose N-acetylcysteine administration on resting state functional connectivity in schizophrenia - Grant McQueen; Aderlee Lay; John Lally; Anthony S. Gabay; Tracy Collier; David J. Lythgoe; Gareth J. Barker; James M. Stone; Philip McGuire; James H. MacCabe; Alice Egerton (Psychopharmacology, 2020)
Rationale There is interest in employing N-acetylcysteine (NAC) in the treatment of schizophrenia, but investigations of the functional signatures of its pharmacological action are scarce. Objectives The aim of this study was to identify the changes in resting-state functional connectivity (rs-FC) that occur following administration of a single dose of NAC in patients with schizophrenia. A secondary aim was to examine whether differences in rs-FC between conditions were mediated by glutamate metabolites in the anterior cingulate cortex (ACC). Methods In a double-blind, placebo-controlled crossover design, 20 patients with schizophrenia had two MRI scans administered 7 days apart, following oral administration of either 2400 mg NAC or placebo. Resting state functional fMRI (rsfMRI) assessed the effect of NAC on rs-FC within the default mode network (DMN) and the salience network (SN). Proton magnetic resonance spectroscopy was used to measure Glx/Cr (glutamate plus glutamine, in ratio to creatine) levels in the ACC during the same scanning sessions. Results Compared to the placebo condition, the NAC condition was associated with reduced within the DMN and SN, specifically between the medial pre-frontal cortex to mid frontal gyrus, and ACC to frontal pole (all p < 0.04). There were no significant correlations between ACC Glx/Cr and rs-FC in either condition ( p > 0.6). Conclusions These findings provide preliminary evidence that NAC can reduce medial frontal rs-FC in schizophrenia. Future studies assessing the effects of NAC on rs-FC in early psychosis and on repeated administration in relation to efficacy would be of interest.

Environmental science and pollution research - Gisela de Aragão Umbuzeiro; Tracy K. Collier (Environmental Science and Pollution Research, 2019)

Effects of N-acetylcysteine on brain glutamate levels and resting perfusion in schizophrenia - Grant McQueen; John Lally; Tracy Collier; Fernando Zelaya; David J. Lythgoe; Gareth J. Barker; James M. Stone; Philip McGuire; James H. MacCabe; Alice Egerton (Psychopharmacology, 2018)

Recent advances in toxicity assessment across taxa - Ruth Sofield; Tracy K. Collier (Environmental Science and Pollution Research, 2017)

Relationships Between Anthropogenic Chemical Contaminant Exposure and Associated Changes in Reproductive Parameters in Male English Sole (Parophrys vetulus) Collected from Hylebos Waterway, Puget Sound, Washington - Sean Y. Sol; Lyndal L. Johnson; Daryle Boyd; O. Paul Olson; Dan P. Lomax; Tracy K. Collier (Archives of Environmental Contamination and Toxicology, 2008)

Contaminant exposure in outmigrant juvenile salmon from Pacific Northwest estuaries of the United States - Lyndal L. Johnson; Gina M. Ylitalo; Mary R. Arkoosh; Anna N. Kagley; Coral Stafford; Jennie L. Bolton; Jon Buzitis; Bernadita F. Anulacion; Tracy K. Collier (Environmental Monitoring and Assessment, 2007)

Biochemical responses to sediment-associated contaminants in brown bullhead (Ameriurus nebulosus) from the Niagara River ecosystem - NANCY A. Eufemia; TRACY K. Collier; JOHN E. Stein; DAVID E. Watson; RICHARD T. Di Giulio (Ecotoxicology, 1997)

Hepatic activities of xenobiotic metabolizing enzymes and biliary levels of xenobiotics in english sole (Parophrys vetulus) exposed to environmental contaminants - Tracy K. Collier; Usha Varanasi (Archives of Environmental Contamination and Toxicology, 1991)

Accumulation and metabolism of carbon-14 labeled benzene, naphthalene, and anthracene by young coho salmon (Oncorhynchus kisutch) - William T. Roubal; Tracy K. Collier; Donald C. Malins (Archives of Environmental Contamination and Toxicology, 1977)